Advanced Applications of Hydrogen and Engineering Systems in the Automotive Industry - Cocco, Luigi; Aziz, Muhammad (IntechOpen, 2021)
The automobile industry is tremendously peculiar due to several strict requirements regarding functional reliability, safety standards, comfort level, high-volume production, and environmental limits. In addition, the industry is experiencing a disruptive evolution of modern vehicle research and design: electrification, connectivity, and autonomous driving. This book provides a robust overview of automotive engineering, including new proposals and the latest trends in road vehicle systems and sub-systems. Each chapter presents a rigorous analysis or a new solution in a clear and concise manner, such that professional and academic readers will appreciate both the theory dissertation and the industrial application.